Evaluating the Impact of Accounting Policies on Risk Management Practices in Insurance Companies: A Comprehensive Analysis of Financial Stability and Performance Metrics - Rusdiah Hasanuddin; Nurasia Natsir (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to critically analyze how accounting policies implemented in insurance companies contribute to effective risk management and overall financial stability. As the business environment becomes increasingly complex and competitive, insurance firms must adopt robust accounting policies that not only facilitate accurate financial reporting but also enhance their ability to identify, assess, and manage various risks. By employing a mixed-methods approach that integrates both qualitative and quantitative data, this research will explore the intricate relationships between accounting policies, risk management strategies, and their subsequent impact on the financial performance of insurance companies. The study will first provide a theoretical framework that outlines the significance of sound accounting practices in the context of risk management. It will then delve into empirical analysis through case studies of selected insurance companies, assessing how their accounting policies influence risk assessment and mitigation processes. Data will be collected via surveys and interviews with key stakeholders, including financial managers, risk officers, and auditors, to gather insights on the effectiveness of these policies in practice. Furthermore, this research will evaluate the correlation between specific accounting practices and key performance indicators, such as profitability, solvency, and liquidity ratios. By identifying best practices and potential areas for improvement, the study aims to offer practical recommendations that can enhance the alignment between accounting policies and risk management efforts. Ultimately, this research seeks to contribute to the existing literature on accounting and risk management in the insurance sector, providing valuable insights that can inform policy formulation and strategic decision-making within the industry. Through this comprehensive evaluation, the study aspires to foster a deeper understanding of how effective accounting policies can serve as a foundation for robust risk management frameworks, thereby promoting long-term financial stability in insurance companies.